Separate and concurrent symbolic predictions of sound features are processed differently - Pieszek, Marika; Schröger, Erich; Widmann, Andreas (Frontiers in Psychology, 2014)
The studies investigated the impact of predictive visual information about the pitch and location of a forthcoming sound on the sound processing. In Symbol-to-Sound matching paradigms, symbols induced predictions of particular sounds. The brain’s error signals (IR and N2b components of the event-related potential) were measured in response to occasional violations of the prediction, i.e. when a sound was incongruent to the corresponding symbol. IR and N2b index the detection of prediction violations at different levels, IR at a sensory and N2b at a cognitive level. Participants evaluated the congruency between prediction and actual sound by button press. When the prediction referred to only the pitch or only the location feature (Exp. 1), the violation of each feature elicited IR and N2b. The IRs to pitch and location violations revealed differences in the in time course and topography, suggesting that they were generated in feature-specific sensory areas. When the prediction referred to both features concurrently (Exp. 2), that is, the symbol predicted the sound´s pitch and location, either one or both predictions were violated. Unexpectedly, no significant effects in the IR range were obtained. However, N2b was elicited in response to all violations. N2b in response to concurrent violations of pitch and location had a shorter latency. We conclude that associative predictions can be established by arbitrary rule-based symbols and for different sound features, and that concurrent violations are processed in parallel. In complex situations as in Exp. 2, capacity limitations appear to affect processing in a hierarchical manner. While predictions were presumably not reliably established at sensory levels (absence of IR), they were established at more cognitive levels, where sounds are represented categorially (presence of N2b).